Evaluation of Policy Impact on Household Waste Management: A Case Study of Marine Pollution at Panipahan Rokan Hilir Port - Hendra Hendra; Febri Yuliani; Adianto Adianto (Department of Public Administration, 2022)
This study aims to determine the impact of household waste management policies at the Panipahan Rokan Hilir port and the role of the Environmental Service in handling household waste in Rokan Hilir. The data analysis used is a qualitative descriptive analysis recommended by Miles and Huberman: Data Reduction, Presentation of Data, and Summarizing and Verification of Results. Data collection techniques include observations, interviews (structured and in-depth with informants), and documentation. The results of the research show that the Evaluation of Policy Impacts in Household Waste Management in a Case Study of Marine Pollution at Panipahan Rokan Hilir Port With the Theory of Policy Impacts, that are: Household Waste Management Policy (Case Study of Pollution at the Panipahan Rokan Hilir Port, it does not have an individual impact on the Panipahan community, both psychological impacts, environmental impacts, economic impacts, and social and personal impacts. No effect on the community in Panipahan, Rokan Hilir Regency, and has not had an impact on social institutions and systems in Panipahan, Rokan Hilir Regency. have done the Task. Its function is from Environmental Pollution Prevention Services and Management of Household Waste and similar Household Wastes quite well. However, it is still not optimal, and this can be seen from the existence of Pollution in the Panipahan Sea due to household waste and similar types of household waste.